Analysis of a G+12 3-dimensional Building Frame Considering Green Building and Energy Efficient Technique using Analysis Tool ETABS - Nayak, Shekhar; Saraswat, Sanjay (International Journal of Scientific Research in Civil Engineering, 2020)
Minimizing energy consumption in buildings has become an important goal in architecture and urban planning in recent years. Guidelines were developed for each climatic zone aiming at increasing solar exposure for buildings in cold climates and at reducing solar exposure for buildings in hot climates. This approach usually plans for the season with the harshest weather; often forgetting that temperatures in cities at latitude 25° can drop below thermal comfort limits in winter and that temperatures in cities at latitude 48° often rise above thermal comfort limits in summer. This paper argues that a holistic approach to energy efficient building forms is needed. It demonstrates a generic energy efficient building form derived by glass walls at exterior and composite wall at the interior.  In this study material replacements were scheduled such as low carbon footprint material replacing a certain percentage of cement in concrete for R.C.C. members.  In this research work for modelling and dynamic analysis ETABS tool is considered.
Keywords: ETABS; Structural Analysis; Energy Efficiency; Low Carbon; Building; Environment